Enhancing performance and managing disruptions in supply chains: The role of dynamic capabilities - Oloruntoba, Richard; Espindola-Rodríguez, Oscar (2023)
Disruptions in supply chains affect the capacity of firms to continue operating normally, satisfying customer requirements, remaining responsive, and attracting revenue. Companies need to develop capabilities that allow them to adapt to changing circumstances and manage disruptions. Dynamic capabilities perspective is valuable for addressing evolving and uncertain environments. This study proposes a model based on findings from a study to empirically evaluate the effect of dynamic capabilities on financial performance and the impact caused by the COVID-19 pandemic using structural equation modelling. Findings suggest agility is a major enabler for increasing financial performance and reducing the negative impacts caused by disruptions.